Sexual Pheromone Induces Diffusion of the Pheromone-Homologous Polypeptide in the Extracellular Matrix of Volvox carteri - Ishida, Koichi (American Society for Microbiology (ASM), 2007)
The C-terminal domain of pherophorin II is homologous to the sexual pheromone of Volvox carteri and is released from other domains during sexual induction. Green fluorescent protein fused to the C terminus of pherophorin II was located at the extracellular matrix directly surrounding the gonidium, the final target of the sexual-induction signal.